The organization of frequency and binaural cues in the gerbil inferior colliculus. Issue 9 (10th March 2017) - Graña, Gilberto David; Hutson, Kendall A.; Badea, Alexandra; Pappa, Andrew; Scott, William; Fitzpatrick, Douglas C.
Abstract: The inferior colliculus (IC) is the common target of separate pathways that transmit different types of auditory information. Beyond tonotopy, little is known about the organization of response properties within the 3‐dimensional layout of the auditory midbrain in most species. Through study of interaural time difference (ITD) processing, the functional properties of neurons can be readily characterized and related to specific pathways. To characterize the representation of ITDs relative to the frequency and hodological organization of the IC, the properties of neurons were recorded and the sites recovered histologically. Subdivisions of the IC were identified based on cytochrome oxidase (CO) histochemistry. The results were plotted within a framework formed by an MRI atlas of the gerbil brain. The central nucleus was composed of two parts, and lateral and dorsal cortical areas were identified. The lateral part of the central nucleus had the highest CO activity in the IC and a high proportion of neurons sensitive to ITDs. The medial portion had lower CO activity and fewer ITD‐sensitive neurons. A common tonotopy with a dorsolateral to ventromedial gradient of low to high frequencies spanned the two regions. The distribution of physiological responses was in close agreement with known patterns of ascending inputs. An understanding of the 3‐dimensional organization of the IC is needed to specify how the single tonotopic representation in the IC central nucleus leads to the multiple tonotopic representations in core areas of the auditory cortex. Abstract : The MRI of a gerbil brain was used to align physiological data from the inferior colliculus on a tissue atlas, graphically illustrating the original locations of recording sites and the organization of characteristic frequencies and interaural time differences.